1995
DOI: 10.1677/joe.0.1470361
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid peroxidation and free radical scavengers in the brain of hyper- and hypothyroid aged rats

Abstract: To determine how lipid peroxides and free radical scavengers are changed in the brain of hyper- or hypothyroid rats, we examined the behavior of lipid peroxide and free radical scavengers in the cerebral cortex of aged (1.5 years old) rats that had been made hyper- or hypothyroid by the administration of thyroxine or methimazol for 4 weeks. Concentrations of catalase, Mn-superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) were increased in hyperthyroid rats compared with euthyroid rats. Concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 12 publications
(15 reference statements)
3
20
0
Order By: Relevance
“…Moreover, an adequate iodine supply for the organism is necessary for optimal thyroid function which is also a requirement for a well-functioning antioxidant defence system. 8,9 The question arises, of whether the eective iodide concentration in our model system can be achieved in vivo through the application of an iodine brine as used in the Austrian spa Bad Hall. The total iodine concentration of the local iodine brine is in the range of about 300 mM.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an adequate iodine supply for the organism is necessary for optimal thyroid function which is also a requirement for a well-functioning antioxidant defence system. 8,9 The question arises, of whether the eective iodide concentration in our model system can be achieved in vivo through the application of an iodine brine as used in the Austrian spa Bad Hall. The total iodine concentration of the local iodine brine is in the range of about 300 mM.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the increase we obtained in oxidant and antioxidant system activities due to hyperthyroidism is consistent with the findings of other researchers. Mano et al 31 investigated lipid peroxidation and free radical elimination mechanisms in cerebral tissues of rats with hyperthyroidism and hypothyroidism. It was reported in their study that the elimination systems compensated for the free radicals formed.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the results of Venditti et al [110] who showed that in all tissues of hypothyroid rats, the malondialdehyde (MDA) levels did not differ significantly from euthyroid values. Mano et al [15] found that the concentration of lipid peroxides, determined indirectly by the measurement of thiobarbituric acid reactants, did not change in hypothyroid rats when compared with the euthyroid animals. Dariyerli et al [227] showed that there is no statistically significant difference found between hypothyroid and control groups in the lipid peroxidation indicator MDA.…”
Section: Antioxidant Statusmentioning
confidence: 99%
“…The changes in the levels of the scavengers -tocopherol, glutathione [15] and coenzyme Q [16] and activities of antioxidant enzymes [11]were found to be imbalanced and often opposite.…”
Section: Introductionmentioning
confidence: 98%